Residual quotient fuzzy subset in near-rings - P. Dheena; S. Coumaressane (International Journal of Mathematics and Mathematical Sciences)
For any fuzzy subsets λ and μ, we introduce the notion of residual quotient fuzzy subset (λ : μ) and we have characterized residual quotient fuzzy subset in near-rings.